Воєнна пропаганда імперії: Перша світова війна та її сучасний відгомін (за матеріалами наукового повідомлення на засіданні Президії НАН України 27 грудня 2023 р.) - Біла, К.В. (Вісник НАН України, 2024)
У статті проаналізовано воєнну пропаганду Російської імперії на теренах
України в період Першої світової війни. Встановлено, що головне завдання воєнної пропаганди імперії полягало у формуванні схвальної рефлексії в
суспільстві на розпочату Росією війну. Метою війни називали визволення
«братніх слов’янських народів», цим міфом виправдовували територіальні претензії Російської імперії в Європі. Використовували й такі прийоми
пропаганди, як перекладання провини за розпочату війну на противника,
створення образу ворога, демонізація ворога, глорифікація війни, героїзація
власного війська, створення образу царя-месії. The article deals with the war propaganda of the Russian Empire during the First World War on the territory of Ukraine.
It was established that the main task of the war propaganda of the empire was to form an approving reflection in society
on the war started by Russia. The goal of the war was called the liberation of the “brotherly” Slavic peoples. This myth
justified the territorial claims of the Russian Empire in Europe. Such propaganda techniques as “shifting the blame for
the started war onto the enemy”, creating an “image of the enemy”, “demonization” of the enemy, “glorification” of war,
“heroization” of one’s own army, creating the image of a “king-messiah” were used. The specificity of Russian war propaganda
was in spreading the myth of the “reunification” or recovering the “ancient” Russian lands, which in fact never
were that. This myth was spread thanks to various historical, ethnographic pseudo-scientific articles that described
Ukrainian territories as “Russian” and their inhabitants as “Russian people”. It is noticeable that the masks of “liberators”,
“defenders of brotherly nations”, fighters for Orthodoxy, fanatical belief in the justice of the war, which appeared in
the imperial mass media, are now also seen in the war propaganda of the Russian Federation. The similarity of the war
rhetoric of the empire with that voiced by the contemporary aggressor evidences not only that 100-year-old war propaganda
techniques are not outdated, but also that imperial ambitions still remain a relevant “stimulus” for Russian society.